A survey of the dialect geography of six towns of La Union Bangar, Bacnotan, San Fernando, Bauang, Tubao and Rosario - Sabado, Consuelo O. 1920- (1970)
The aim of the study is to make a survey of the dialect geography of six major towns of La Union namely Bangar, Bacnotan, San Fernando, Bauang, Tubao and Rosario. It is concerned in finding the differences in forms of words having similar meanings.
Thesis (M.A.T.Pilipino)--University of the Philippines, Diliman.
Keywords: Iloko languages -- Dialects; La Union -- Languages -- Maps